The animator's sketchbook - Pixar (Firm); Walt Disney Enterprises (San Francisco : Chronicle Books, 2015)
"Creating an animated film takes a lot of work, from the texture of a character's hair to the shot sequence of a high-speed car chase. This Pixar-branded sketchbook is comprised primarily of blank pages for animators of all skill levels to fill in with ideas, storyboards, and sketches. Conveniently divided based on the core preproduction stages of Concept, Color, Story, Characters, and Worlds, each section begins with a brief introduction, a handful of inspiring quotes from some of the best artists working at Pixar, and a few key examples of related art before launching into blank templates, ready to be filled. Useful and inspiring, this journal provides a structured space for aspiring filmmakers to workshop their ideas through all phases of development."
Keywords: Animated films; Animators -- Notebooks, sketchbooks, etc